Respuesta :

Step-by-step explanation:

All steps are in picture.

If you have any question about it you can ask.

Thanks

Ver imagen ma5007482
Ver imagen ma5007482
Ver imagen ma5007482
Ver imagen ma5007482

#a

  • a(1)=1
  • a(n)=3a(n-1)

[tex]\\ \sf\longmapsto a(2)=3a(1)=3(1)=3[/tex]

[tex]\\ \sf\longmapsto a(3)=3a(2)=3(3)=9[/tex]

[tex]\\ \sf\longmapsto a(4)=3a(3)=3(9)=27[/tex]

[tex]\\ \sf\longmapsto a(5)=3a(4)=3(27)=81[/tex]

#b

  • b(1)=1
  • b(n)=-2+b(n-1)

[tex]\\ \sf\longmapsto b(2)=-2+b(1)=-2+1=-1[/tex]

[tex]\\ \sf\longmapsto b(3)=-2+b(2)=-2-1=-3[/tex]

[tex]\\ \sf\longmapsto b(4)=-2+b(3)=-2-3=-5[/tex]

[tex]\\ \sf\longmapsto b(5)=-2-5=-7[/tex]

Ver imagen Аноним
ACCESS MORE